2022
DOI: 10.3389/fcell.2022.878142
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Mechanisms Supporting Neuronal Polarity From Small Animals to Humans

Abstract: Axon-dendrite formation is a crucial milestone in the life history of neurons. During this process, historically referred as “the establishment of polarity,” newborn neurons undergo biochemical, morphological and functional transformations to generate the axonal and dendritic domains, which are the basis of neuronal wiring and connectivity. Since the implementation of primary cultures of rat hippocampal neurons by Gary Banker and Max Cowan in 1977, the community of neurobiologists has made significant achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 167 publications
(272 reference statements)
0
2
0
Order By: Relevance
“…3A. The results showed that on CHI1 there was an extension in the first hours and then a retraction, but this behavior is typical of minor processes during Stage 2 (12-24 h) (Miyata et al, 2005) that precedes Stage 3 in which a minor process begins to grow rapidly and transforms into an axon (symmetry break) (Wilson et al, 2022).…”
Section: Average Length Of Minor Neurites Average Length Of Major Neu...mentioning
confidence: 92%
“…3A. The results showed that on CHI1 there was an extension in the first hours and then a retraction, but this behavior is typical of minor processes during Stage 2 (12-24 h) (Miyata et al, 2005) that precedes Stage 3 in which a minor process begins to grow rapidly and transforms into an axon (symmetry break) (Wilson et al, 2022).…”
Section: Average Length Of Minor Neurites Average Length Of Major Neu...mentioning
confidence: 92%
“…Studies on cultured hippocampal and cortical neurons that develop in situ have established that the generation of an axon from a rather symmetric array of short and highly dynamic undifferentiated neurites is one of the early events underlying the establishment of morphological polarity (Caceres et al, 2012; Funahashi et al, 2014; Wilson et al, 2022). Current evidence favors the view that an increase in actin dynamics and growth cone size selects a minor neurite to become the axon (Bradke and Dotti, 1997, 1999; Kunda et al, 2001).…”
Section: Introductionmentioning
confidence: 99%